The Research on the Empowerment Mechanism of Private Enterprise Led to Entrepreneurial Ecosystem -Taking Qilu Yunshang E-Commerce Industrial Park as an Example - Qian, Kong (Journal of Roi Kaensarn Academi, 2024)
The goals of this study are: 1) to explore the construction and empowerment process of private enterprise-led entrepreneurial ecosystems; 2) to analyze the empowerment mechanisms of entrepreneurial ecosystems at different stages of development and their impact on the growth of start-ups. The sample is the entrepreneurial ecosystem of Qilu Cloud Commerce E-commerce Industrial Park, selected by private enterprises, and the research instrument used for data collection is a single-case longitudinal tracking study. Data analysis statistics are based on the analytical framework of “empowerment pathways – empowering actions – entrepreneurial performance”. The research results are as follows: 1) The empowerment evolution process of the entrepreneurial ecosystem shows the gradual characteristics of "structural empowerment: resource patchwork - leadership empowerment: resource orchestration - psychological empowerment: resource synergy"; 2) The system has been constructed A theoretical model that empowers the growth of start-ups; 3) Suggestions are put forward to improve the construction of the entrepreneurial ecosystem and promote the high-quality development of innovation and entrepreneurship.